The cost-effectiveness of radiofrequency ablation for Barrett's esophagus with low-grade dysplasia: Results from a randomized controlled trial (SURF trial) - RAVI, NARAYANASAMY (My University, 2016)
Background and Aims The Surveillance versus Radiofrequency Ablation (SURF) trial randomized 136 patients with Barrett's esophagus (BE) containing low-grade dysplasia (LGD), to receive radiofrequency ablation (ablation, n = 68) or endoscopic surveillance (control, n = 68). Ablation reduced the risk of neoplastic progression to high-grade dysplasia and esophageal adenocarcinoma (EAC) by 25% over 3 years (1.5% for ablation vs 26.5% for control). We performed a cost-effectiveness analysis from a provider perspective alongside this trial.
IN_PRESS
Keywords: Surveillance versus Radiofrequency Ablation (SURF) trial; Surveillance versus Radiofrequency Ablation (SURF) trial